Role-Playing Method In Developing Islamic Student’s Entrepreneurship Mentality - Nur Rizqi Febriandika; Sisna Gaida (LPPM ISNJ Bengkalis, 2021)
The purpose of this study is to determine the application of the role-playing method as well as supporting and inhibiting factors in fostering the entrepreneurial mentality of students in the